Different Approaches for Evaluation and Modeling of the Effective Thermal Resistance of Groundwater-Filled Boreholes - Oleg Todorov (MDPI AG, 2021)
Groundwater-filled boreholes are a common solution in Scandinavian installations of ground source heat pumps (GSHP) due to the particular hydro-geological conditions with existing bedrock, and groundwater levels close to the surface. Different studies have highlighted the advantage of water-filled boreholes compared with their grouted counterparts since the natural convection of water within the borehole tends to decrease the effective thermal resistance Rb*. In this study, several methods are proposed for the evaluation and modeling of the effective thermal resistance of groundwater-filled boreholes. They are based on distributed temperature sensing (DTS) measurements of six representative boreholes within the irregular 74-single-U 300 m-deep borehole field of Aalto New Campus Complex (ANCC). These methods are compared with the recently developed correlations for groundwater-filled boreholes, which are implemented within the python-based simulation toolbox Pygfunction. The results from the enhanced Pygfunction simulation with daily update of Rb* show very good agreement with the measured mean fluid temperature of the first 39 months of system operation (March 2018–May 2021). It is observed that in real operation the effective thermal resistance Rb* can vary significantly, and therefore it is concluded that the update of Rb* is crucial for a reliable long-term simulation of groundwater-filled boreholes.